Novel 2,6-diformyl-4-methyl phenol based chemosensor for Zn-II ion by ratiometric displacement of Cd-II ion and its application for cell imaging on human melanoma cancer cells - Mitra, Debarshan; Venkatathari, N.; Sabharwal, S. C.; Godbole, S. V.; Tyagi, A. K.; Das, Sangbrita (Journal of the Indian Chemical Society, 2015)
A new chelating ligand [4-methyl-2,6-bis-(pyridin-2-yl-hydrazonomethyl)-phenol] (1) was prepared by the condensation of 2-hydrazinylpyridine with 2,6-diformyl-p-cresol. Compound 1 exhibits weak fluorescence due to intramolecular photoinduced electron transfer (PET). The sensor (1) demonstrates Zn2+-specific emission enhancement due to ``PET off'' process through a 1 : 1 binding mode with the metal ion. The fluorescence quantum yield of the chemosensor 1 is only 0.020, and it increases more than 14-fold (0.280) in the presence of one equivalent of the zinc ion. Interestingly, the introduction of other metal ions causes the fluorescence intensity to remain either unchanged or weakened except for Cd2+. Ratiometric displacement of Cd2+ ion from the complex by Zn2+ ion supports the formation of more stable sensor-Zn2+ complex over the sensor-Cd2+ complex. The experimental findings have been correlated with theoretical results using B3LYP functional and 6-31G(d,p), LANL2DZ basis set for Cd2+ (2) and Zn2+ (3) complex, respectively, by Density Functional Theory (DFT) method. Moreover, the ability of probe 1 to sense Zn2+ within human melanoma cancer cells has been explored, and the Zn2+-probing process in living cells was reversible. [Mn-2(PHMP)(2)](ClO4)(2) (4) and [Ni-2(PHMP)(H2O)(5)](NO3)(3) (5) have been also synthesized and characterized crystallographically and spectroscopically to understand the ligating behavior of the ligand PHMP.
Keywords: Cd-II ion; Chemosensor; Density functional theory; human melanoma cancer cells; photoinduced electron transfer; Zn-II ion

Bicinchoninic acid-based colorimetric chemosensor for detection of low concentrations of cyanide - Biradar, Archana A.; Biradar, Ankush V.; Sun, Tiffany; Chan, Yung; Huang, Xiaoxi; Asefa, Tewodros (Sensors and Actuators B-Chemical, 2016)
Bicinchoninic acid (BCA) is reagent that is widely used to determine the concentration of proteins in solutions through the colored complex it forms with Cu(I) and the proteins. In this report, we present a new use for BCA, where a highly sensitive method for detection of cyanide ions in solutions by using Cu2+-BCA complex as the chemosensing agent is demonstrated. The detection of cyanide ions is achieved by taking advantage of the nucleophilic attack of the Cu2+-BCA complex by cyanide ions. Upon the addition of cyanide ions, the Cu2+-BCA complex undergoes transformations to free BCA via a series of equilibriums and, as a result, forms different Cu(II)-(BCA)(x)(CN)(y) species depending on the concentrations of cyanide ions in the solution. These different Cu(II)-(BCA)(x)(CN)(y) species, in turn, give different metal-to-ligand charge transfer electronic spectra and colors that are easily detectable both with naked eyes and UV-vis spectroscopy. As the cyanide ion concentration increases, the color of the solution containing the complexes changes from green to purple, red, yellow, and finally colorless, giving a corresponding blue shift in the absorption maxima on their UV-vis spectra. Through this process, the complexes enable detection of cyanide ions with a detection level of up to 0.06 ppm in solutions. Thus, this colorimetric technique based on Cu2+-BCA can make low concentrations of cyanide detectable, well before the concentrations possibly reach lethal amounts. Furthermore, the method is shown to give fast detection response with no interference from other anionic and cationic species and has the potential to be adopted for accurate and convenient analysis of cyanide ions in drinking water sources as well as industrial effluents. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BCA; Bicinchoninic acid; Chemosensor; Colorimetric sensor; Copper; Cyanide

Naphthoquinone based chemosensor 2-(2 `-aminoethylpyridine)-3-chloro-1,4-naphthoquinone: detection of metal ions, X-ray -crystal structures and DFT studies - Patil, Amit; Ware, Anuja P.; Bhand, Sujit; Chakravarty, Debamitra K.; Gonnade, Rajesh G.; Pingale, Subhash S.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2016)
Naphthoquinone based Chemosensor 2; 2-(2'-aminoethylpyridine)-3-chloro-1,4-napthoquinone have been synthesized and characterized. Chemosensor 2 crystallizes in the orthorhombic space group Pbcn and shows extensive intramolecular as well as intermolecular hydrogen bonding interactions. Each molecule of Chemosensor 2 showed interaction with five neighboring molecules via C-H center dot center dot center dot N, N-H center dot center dot center dot N, C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions. Slipped pi-pi stacking interaction was observed in adjacent quinonoid and benzenoid rings. Chemosensor abilities of Chemosensor 2 ligand have been evaluated with metal ions viz. Cu2+, Ni2+, Zn2+, Co2+, Fe3+, Mn2+, Cr3+, Hg2+, La3+ and Cd2+ in methanol, methanol-water mixture and in presence of mild base triethylamine. Stoichiometry of Chemosensor 2 with metal ions such as Cu2+, Ni2+, Zn2+ and Co2+ ions was determined by Jobs method in methanol and were found as 1:1 for Cu2+ and 2:1 for Ni2+, Zn2+ Co2+. The variation in the metal ligand ratio is observed in aqueous media for Cu2+. Chemosensor 2 can be used selectively for naked eye detection of Cu2+ ions. The association constant obtained in methanol shows the trend Cu2+>Ni2+>Co2+. Cu2+ and two (Ni-1 and Ni-2) Ni2+ complexes were synthesized. Ni-2 complex showed coordination of Chemosensor 2 ligands was through pyridine nitrogen's only. The Chemosensor 2 and its deprotonated forms in methanol, water and triethylamine were also studied by TD-DFT studies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Chemosensor; hydrogen bonding; Naphthoquinone; pi-pi stacking; TD-DFT

Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors